Agroecology and corporate power in the U.S. - Lloyd, Sarah; Treakle, Jordan; Hendrickson, Mary (Journal of Agriculture, Food Systems, and Community Development, 2024)
First paragraph: Introduction In reflecting on the U.S. Agroecology Summit 2023, we want to bring a key issue to the fore: corporate power and how agroecology can address it in the food system. Taking on existing power structures was an important theme running through the conference, from confronting legacies of colonization and slavery in the food system to battling the marginalization of affected communities in agricultural and food sciences. The corporate dominance of agricultural markets and its corresponding influence in the political realm was certainly present throughout our discussions, but here we want to center the role of corporate power in future discussions of agroecology in the U.S. . . .